La justice constitutionnelle en France - Favoreu, Louise (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
The 1958 Constitution provided France with a constitutionally based system of justice and although this had been contrary to French traditions — and consequently apprehended at that time — the system has progressively developed and become one of the main elements of the French constitutional regime and at the same time, one of its most dynamic and appreciated components. This article presents the French Constitutional Council: its status, composition and operations. It maps out areas in which this body has had to intervene and, above all, it analyses the jurisprudence of the Council and notes that its most impressive contribution lies in the field of the constitutional review of laws and its main objective, basic personal freedoms. The conclusion of this study is that French constitutional law has undergone radical modifications under this system and that in the future, it has become a fertile ground for comparative studies for the Canadian jurist due to the constitutional review of laws in the name of personal freedoms.